2016
DOI: 10.1038/cgt.2015.67
|View full text |Cite
|
Sign up to set email alerts
|

IL-15/sIL-15Rα gene transfer suppresses Lewis lung cancer growth in the lungs, liver and kidneys

Abstract: Nearly 40% of people with lung cancer have tumor growth in other organs at the time of diagnosis. Current treatment strategies for patients with late-stage lung cancer are primarily palliative and only showed modest efficacy. The current study takes advantage of the hydrodynamic gene delivery technique to evaluate the antitumor activity of interleukin (IL)-15/sIL-15Rα on lung tumors growing in the lungs, liver and kidneys. We demonstrate that hydrodynamic tail vein injection of 2 μg of AG209 DP muIL-15sRα+IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The contained IL-15 Rα was modified at a post-translational level intracellularly, mostly by O - and N -linked glycosylation and thus boosted, but not inhibited, IL-15 bioactivity as compared to exogenous soluble IL-15 Rα (26, 27). This contention is further supported by further studies that employed plasmids co-expressing IL-15 and the extracellular domain of IL-15 Rα (28, 29). …”
Section: Il-15 Superagonist Fusion Proteinmentioning
confidence: 80%
See 1 more Smart Citation
“…The contained IL-15 Rα was modified at a post-translational level intracellularly, mostly by O - and N -linked glycosylation and thus boosted, but not inhibited, IL-15 bioactivity as compared to exogenous soluble IL-15 Rα (26, 27). This contention is further supported by further studies that employed plasmids co-expressing IL-15 and the extracellular domain of IL-15 Rα (28, 29). …”
Section: Il-15 Superagonist Fusion Proteinmentioning
confidence: 80%
“…In a simple way, systemic injection with plasmid co-expressing murine IL-15/murine IL-15 Rα complex resulted in production of serum IL-15/IL-15 Rα at a level sufficient to inhibit tumor growth of metastatic lung and hepatocellular cancer and significantly improved long-term survival, especially when combined with chemotherapy (29). Cheng and colleagues delivered IL-15/IL-15 Rα-expressing adenovirus in a model of hepatocellular carcinoma as an effective way to cause regression of hepatic metastases (28) (Table IV).…”
Section: Engineered Cells Expressing Il-15/il-15 Rα Complex: Genmentioning
confidence: 99%
“…Chemotherapy can enhance anti-tumor responses by reducing tumor burden, inducing release of tumor antigens upon tumor cell death, and reducing immunosuppressive populations. In multiple murine tumor models, the combination of IL-15 stimulation plus chemotherapy results in increased tumor regression, prolonged survival, and protection against tumor recurrence as compared to chemotherapy alone [6870]. Cyclophosphamide (CY) treatment can induce remission in mice given 76-9 rhabdomyosarcoma cells locally.…”
Section: Using Il-15 In Combinationmentioning
confidence: 99%
“…Since IL-15 has been shown to induce the production of TNF-α and IFN-γ from T cells and NK cells [71,72], the administration of IL-15 after CY injection may further promote the production of Th1-related cytokines induced by CY. In addition to CY, IL-15 has also been shown to potentiate the anti-tumor activity of other chemotherapeutic agents, such as 5-fluorouracil, leucovorin, and gemcitabine [73,70]. Since gemcitabine induces a dramatic reduction in the number of MDSCs [74,75], this may be an example of how IL-15 stimulation can be more effective when immune suppression is removed.…”
Section: Using Il-15 In Combinationmentioning
confidence: 99%
“…These authors achieved an increase in NK cell count, as also reported by Barao et al [ 72 ] and an increase in the number of memory CD8 lymphocytes in blood, spleen and liver—with modest therapeutic effects against colon cancer, for 60 days. Sun et al [ 73 ] evaluated the antitumor activity of IL15/sIL15Rα upon Lewis lung tumour growth in lungs, liver and kidney. They transferred this gene as DNA plasmid, reporting inhibition of tumour growth in all three organs and prolonged survival time.…”
Section: Gene Transfer Applicationsmentioning
confidence: 99%